ERG and CHD1 heterogeneity in prostate cancer: Use of confocal microscopy in assessment of microscopic foci. Issue 15 (29th August 2014) - Tereshchenko, Irina V.; Zhong, Hua; Chekmareva, Marina A.; Kane‐Goldsmith, Noriko; Santanam, Urmila; Petrosky, Whitney; Stein, Mark N.; Ganesan, Shridar; Singer, Eric A.; Moore, Dirk; Tischfield, Jay A.; DiPaola, Robert S.
<x xml:space="preserve">Abstract</x> BACKGROUND Biomarkers predicting tumor response are important to emerging targeted therapeutics. Complimentary methods to assess and understand genetic changes and heterogeneity within only few cancer cells in tissue will be a valuable addition for assessment of tumors such as prostate cancer that often have insufficient tumor for next generation sequencing in a single biopsy core. METHODS Using confocal microscopy to identify cell‐to‐cell relationships in situ, we studied the most common gene rearrangement in prostate cancer (TMPRSS2 and ERG) and the tumor suppressor CHD1 in 56 patients who underwent radical prostatectomy. RESULTS Wild type ERG was found in 22 of 56 patients; ERG copy number was increased in 10/56, and ERG rearrangements confirmed in 24/56 patients. In 24 patients with ERG rearrangements, the mechanisms of rearrangement were heterogeneous, with deletion in 14/24, a split event in 7/24, and both deletions and split events in the same tumor focus in 3/24 patients. Overall, 14/45 (31.1%) of patients had CHD1 deletion, with the majority of patients with CHD1 deletions (13/14) correlating with ERG‐rearrangement negative status (P < 0.001). CONCLUSIONS These results demonstrate the ability of confocal microscopy and FISH to identify the cell‐to‐cell differences in common gene fusions such as TMPRSS2–ERG that may arise independently within the same tumor focus. These data support the need to study complimentary approaches to assess genetic changes that may stratify therapy based on predicted sensitivities. Prostate 74:1551–1559, 2014. © 2014 Wiley Periodicals, Inc.